Easy access to bright oxygen defects in biocompatible single-walled carbon nanotubes via a Fenton-like reaction - Settele, Simon; Stammer, Florian; Sebastian, Finn; Lindenthal, Sebastian; Wald, Simon; Li, Han; Flavel, Benjamin S.; Zaumseil, Jana (ACS nano, 2024)
The covalent functionalization of single-walled carbon nanotubes (SWNTs) with luminescent oxygen defects increases their brightness and enables their application as optical biosensors or fluorescent probes for in vivo imaging in the second-biological window (NIR-II). However, obtaining luminescent defects with high brightness is challenging with the current functionalization methods due to a restricted window of reaction conditions or the necessity for controlled irradiation with ultraviolet light. Here, we report a method for introducing luminescent oxygen defects via a Fenton-like reaction that uses benign and inexpensive chemicals without light irradiation. (6,5) SWNTs in aqueous dispersion functionalized with this method show bright E11* emission (1105 nm) with 3.2 times higher peak intensities than the pristine E11 emission and a reproducible photoluminescence quantum yield of 3%. The functionalization can be performed within a wide range of reaction parameters and even with unsorted nanotube raw material at high concentrations (100 mg L−1), giving access to large amounts of brightly luminescent SWNTs. We further find that the introduced oxygen defects rearrange under light irradiation, which gives additional insights into the structure and dynamics of oxygen defects. Finally, the functionalization of ultrashort SWNTs with oxygen defects also enables high photoluminescence quantum yields. Their excellent emission properties are retained after surfactant exchange with biocompatible pegylated phospholipids or single-stranded DNA to make them suitable for in vivo NIR-II imaging and dopamine sensing.